COMMUNITY ACTION PLAN (CAP) DALAM PENATAAN KAWASAN KUMUH DARI PERSPEKTIF GOOD URBAN GOVERNANCE: SEBUAH TINJAUAN LITERATUR - Muslim, Ardila; Kurniawan, Teguh (ipdn, 2020)
Urban slums is one of the main issues that developing countries discussed nowadays, whether to eliminate slums area or through sustainable development policies and official rental housing policies. One of the method is the CAP method as a way to build a community that could take actions in accordance with problems, needs and potential resources. However, the CAP method requires a good governance because it involves government, citizens, social and private organizations. Through a literature study approach, this research expects to obtain a framework and relevant theory to the implementation of the Community Action Plan (CAP) in the slum area management with the perspective of good urban governance. The analysis results shows that the CAP can be implemented for management of slums area through the stages of preparation, social environmental mapping, and approval of the CAP and a new layout map. However, the implementation must confirm four domains of constrains to assess a good urban governance, such: responsibility, accountability, representation, access, strength, legitimacy and effectiveness. This results in governance that is not only responsive and effective, but also resilient, reliable and balanced.